Comparison of high‐speed transportation systems in special consideration of investment costs - Schach, Rainer; Naumann, René (Transport, 2007)
In this paper a substantial comparison of different high‐speed transportation systems and an approach to stochastic cost estimations are provided. Starting from the developments in Europe, the high‐speed traffic technical characteristics of high‐speed railways and Maglev systems are compared. But for a comprehensive comparison more criterions must be included and led to a wider consideration and the development of a multi‐criteria comparison of high‐speed transportation systems. In the second part a stochastic approach to cost estimations of infrastructure projects is encouraged. Its advantages in comparison with the traditional proceeding are presented and exemplify the practical implementation.First Published Online: 27 Oct 2010